Can lymphocytes serve as a predictor of response to preoperative chemoradiation therapy for locally advanced rectal cancer? - Lutsyk, Myroslav; Taha, Tarek; Billan, Salem (Frontiers in Oncology, 2023)
Introduction: The aim of this study is to identify factors that may predict the response of locally advanced rectal cancer tumors (LARC) to neoadjuvant chemoradiotherapy (CRT) and to evaluate the effect of circulating lymphocytes on pathological tumor response. Methods: This retrospective study included neoadjuvant CRT-treated, LARC-diagnosed patients at the Rambam Health Care Campus in Haifa, Israel. CHAID analysis, t-test, χ2 test, and ROC curve analyses were performed to explore the association between pathological complete response (pCR) and several factors including patient demographics, tumor characteristics, type of treatment, and levels of circulating lymphocytes measured on a weekly basis. Results: Out of 198 patients enrolled in the study, pCR was achieved in 50 patients (25%). ROC curve and CHAID analyses showed that absolute lymphopenia was significantly associated with lower pCR rates (p=0.046 and p=0.001, respectively). Other factors that were found to have a significant impact were radiation therapy type (p=0.033) and tumor distance from the anal verge (p= 0.041). Conclusions: An absolute decrease in the level of circulating lymphocytes during preoperative CRT to LARC is associated with poorer tumor response to treatment and thus may serve as a predictive biomarker for treatment resistance.